Performance evaluation of glass wool core VIPs and silica-fly ash core VIPs. (May 2022) - Shahzad, Asim; Chen, Zhaofeng; Khan, Zaffar M; Emefa Awuye, Desire
Temperature maintenance is one of the leading factors for the large-scale energy consumption in buildings, which accounts for 33% of the total consumption. The heavy smog in China resulting from the depletion of fossil fuels necessitates the development of new technologies that can reduce the energy usage in buildings. Several techniques for building's thermal insulation were developed among which the utilization of Vacuum Insulation Panels (VIPs) has the leading edge. For refrigeration purpose in VIPs, the glass wool is being used as a core material because of their low thermal conductivity (λ ≤ 2 mW/m·K) and low cost. However, the silica-fly ash has been preferred as a core material of VIPs for buildings because of its high compressive strength (σc > 2 MPa) and the most economical price. Moreover, the P 1/2 of the glass wool VIP and silica-fly ash VIP are 10–100 and 1000 Pa, respectively. In this work, the performance of VIPs with various cores has been compared. The thermal conductivity of VIPs, along with the factors affecting thermal conductivity, such as density, thickness, internal pressure, and porous structures, have been evaluated. In addition, the effect of core materials on the cost of VIPs was also quantified. It is expected that the study will serve as a pioneering work in the foundation to development of the next-generation, low-cost VIPs used for building insulations.